MODELING DYNAMIC ADSORPTION ISOTHERMS AND THERMODYNAMIC PROPERTIES OF SPECIALTY GROUND ROASTED-COFFEE (Coffee Arabica L.) - Collazos-Escobar, Gentil Andres; Gutiérrez-Guzman, Nelson; Vaquiro Herrera, Henry A. (Coffee Science - ISSN 1984-3909, 2019)
Specialty coffee is highly differentiated product because of its sensorial attributes: aroma, body and brand reputation. In specialized markets, these products are highly valued, and sometimes up to six times their commercial value is paid. Thus, it is essential to preserve their freshness. Sorption isotherms are necessary for determining and studying water sorption changes in specialty coffee during storage. This study aimed to determine the adsorption isotherms of specialty ground roasted-coffee at temperatures of 25 °C, 30 °C and 40 °C and water activities between 0.1 and 0.8 using the dynamic dewpoint method (DDI). The experiment sorption data were modeled using 12 different equations with non-linear regression to represent the dependence of the equilibrium moisture content with both water activity and temperature. In addition, the thermodynamic properties were determined with the experiment adsorption data. The results showed that type III isotherms were obtained according to the Brunauer classification, and the Weibull equation satisfactorily modeled the effect of the temperature on the hygroscopic equilibrium in the specialty ground roasted-coffee. The results of thermodynamic analysis showed that the net isosteric heat of adsorption and Gibbs free energy decreased as the equilibrium moisture content increased, indicating the amount of energy released, a strong bond energy between water molecules in the product components and spontaneity in the adsorption process. The entropy of the adsorption increased with the moisture content, leading to product stability conditions during storage. The results were similar to those reported for the roasted and ground coffee of others cultivars.